PENGARUH KELUARGA DAN KELOMPOK REFERENSI TERHADAP KEPUTUSAN KONSUMEN MEMBELI KOSMETIKA KHUSUS PRIA MEREK GARNIER MEN (STUDI KASUS DI PEKANBARU) - Debora, Ris; Sulistyowati, Lilis; Musfar, Tengku Firli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research is conducted to test the influences of family and reference group which are contained of Friendship, Working, Purchase, Consumer-action, and Web Group towards purchase intention of Garnier Men cosmetics in Pekanbaru. Samples of this research are Garnier Men’s consumer from both teenagers and men in Pekanbaru. Samples are chosen by using some sort of method and it were both only self-purchase and mature user above 17 years old. In this research, linear regression method is chosen for data analysis by SPSS version 20 and the the result shows that there are some affecting variables which didn’t significantly affect purchase intention of Garnier Men cosmetics in Pekanbaru. Family and Friendship Group are the only affecting variables that significantly affect purchase intention of Garnier Men in Pekanbaru.Keywords: Family, Reference Group, Friendship, Working, Purchase, Consumeraction, Web, Purchase Intention